Rancang Bangun Webgame Interaktif Pada Matakuliah Bahasa Inggris Maritim Menggunakan Model View Controller (MVC) - Fajar Sari Kurniawan; Dhesi Wulan Sari; Purwanto Purwanto (Politeknik Harapan Bersama, 2025)
Maritime English has been internationally recognized to reduce the risk of misunderstandings that could lead to fatal incidents and to ensure that safety procedures are correctly implemented regardless of nationality. English language learning focusing on Standard Marine Communication Phrases (SMCP) at maritime schools aims to prepare students for effective and safe maritime communication. However, conventional learning methods are often perceived as uninteresting and boring, causing students to pay less attention and reducing material comprehension. Therefore, it is necessary to create a new learning environment through the development of educational media that provides innovative and interactive learning experiences. This research proposes an educational webgame developed using the Software Development Life Cycle (SDLC) model, which includes needs analysis, system design, development, testing, and maintenance. The webgame was implemented using PHP programming language with the CodeIgniter 3 framework, employing the Model-View-Controller (MVC) architecture and MySQL database for consistent data processing. JavaScript and jQuery were integrated to enhance user interaction and expedite HTML element manipulation. System testing revealed no errors or functional deviations, indicating stable operation. User validation involving students yielded a good response rate, with a satisfaction score of 85.46%, confirming the feasibility of the webgame as a digital-based interactive learning tool. The webgame-based learning media has proven to increase student engagement and interest in learning maritime English, making it a promising solution to improve the effectiveness of maritime English instruction and support safety communication competencies.